Impact of Dietary Intake and Cardiorespiratory Fitness on Glycemic Variability in Adolescents: An Observational Study - Mingliang Ge; Stephanie R Lebby; Shivani Chowkwale; Caleb Harrison; Grace M Palmer; Keith J Loud; Diane Gilbert-Diamond; Mary Ellen Vajravelu; Jennifer L Meijer (Current Developments in Nutrition)
Background: Cardiorespiratory fitness (CRF), estimated by maximum oxygen consumption (VO2 max) during exercise, is worsening among adolescents and associated with a decline in metabolic health into adulthood. Glycemic patterns may provide a mechanism between CRF and health. Objectives: This study assessed the feasibility of measuring glycemic patterns using continuous glucose monitoring (CGM) in adolescents, aged 14–22 y, to estimate the relationship between VO2 max and glucose patterns. Methods: Healthy adolescents (n = 30) were recruited for a treadmill VO2 max test and to complete the following activities for 7–10 d: 1) wear a Dexcom G6 CGM, 2) complete ≥3 24-h dietary recalls, and 3) complete 1 at-home oral glucose tolerance test (OGTT, 75 g glucose). Glycemic patterns were extracted as mean glucose, the coefficient of variance, the mean amplitude of glycemic excursions, and the mean of daily differences. The 2-h glucose responses to the OGTT and individual meals were extracted. Statistical analyses evaluated the relationship between VO2 max and 1) overall glycemic patterns and 2) the maximum glucose level and AUC response to OGTT and meals, stratified by sex. Results: Participant feasibility demonstrated that 90% completed CGM data (n = 27), 87% ≥7 d of CGM data (n = 26), 97% attempted OGTT (n = 29), and 93% completed ≥3 dietary recalls (n = 28). Most participants had normal BMI (70%) with an even distribution of sex (44% male). Males exhibited an inverse relationship between VO2 max and overall mean glucose (ß= –7.7, P = 0.04). Males demonstrated an inverse relationship between VO2 max and 1) maximum glucose (ß = –29, P = 0.006) and AUC (ß = –2702, P = 0.001) in response to the OGTT and 2) AUC (ß = –1293, P = 0.03) in response to meals. No association was observed between VO2 max and glucose patterns in females. Conclusions: A sex-specific relationship between VO2 max and glycemic patterns was observed, suggesting a unique metabolic capacity during late adolescence by sex.This trial was registered at clinicaltrials.gov as NCT05845827.